Factors Impacting Work Family Balance of Working Mothers - Arri Handayani; Tina Afiatin; M. G. Adiyanti; Fathul Himam (ANIMA Indonesian Psychological Journal, 2015)
Most working women find it difficult to get work-family balance because when they are in one domain, the other suffers. Work-family balance will be useful for organization, family, and the individual himself. This research was aimed at finding out factors that influence workfamily balance of working mothers in Semarang, using descriptive qualitative method. The research subject was selected using purposive technique with informant characteristics as follow: working mother, working husband, living together with husband, and having child under 18 years old. Based on the research result, it was revealed that there are six factors influencing work-family balance, either from internal or external factors. Internal factors that influence work-family balance are commitment, understanding towards women’s role, and individual’s character. Meanwhile, external factors that influence work-family balance are social support, either from husband, family, supervisor, or colleagues, the presence of a child, and working autonomy.